Análisis de cumplimiento tributarío para una cooperativa de ahorro y crédito cerrada ubicada en la ciudad de Guayaquil para el periodo fiscal 2008 - González, María Virginia (2010)
This paper contains an Analysis of an institution Tax financial sector nonprofit whose sole purpose is to coordinate actions and efforts of an economic, intellectual, social and moral development of its partners. The evaluation was did on account balances that were used for the payment of taxes such as Income Tax, IVA, Retention to the source, Retention of IVA in the period to December 31, 2008. It was also verified the payment of such taxes within the deadlines set in the Organic Law of the Internal Tax Regime and its regulations. The overall goal was raised a report or memorandum of tax compliance to the Savings and Credit Cooperative “Mathew Ltda”, was defined specific objectives, programs, procedures and auditing techniques such as the review of Support Documents, testing , establishment of samples and data collection. etc. The analysis was obtained that the deductible expense of the Cooperative for 2008 was lower than the value declared on Form 101 Statement of Income Tax for that year.